DEVELOPMENT OF ANDROID-BASED EDUCATIONAL MEDIA TO IMPROVE THE CALISTUNG ABILITY OF GRADE 2 ELEMENTARY SCHOOL STUDENTS - Hanifah Nurjanah; Isrok’atun; Rana Gustian Nugraha (Perspektif Ilmu Pendidikan, 2023)
The rapid development of the times, the flow of globalization is increasingly affecting all aspects of every aspect of human life, especially in the world of education. This is because the development of science and technology has played a very important role in the learning process of students at school. Therefore, research was conducted to answer challenges in understanding digital literacy which is still low with a focus on increasing calistung abilities. The study used the ADDIE method with descriptive-quantitative data analysis. The subject of the research trial was carried out to grade II elementary school students at SDN Cimekar and SDN Mekarwangi in Cileunyi District, Bandung Regency. Data was collected through field observation stages, written tests in the form of giving pretest & posttest questions to students and questionnaires to expert figures. In this study, it produced a percentage value of 92.86% in a very good category by media expert lecturers and a percentage value of 90% which had a good category even though revisions were delivered by material experts on the application display and material vocabulary. The pretest & posttest questions received an interpretation value of "enough" and all the questions tested were declared valid. This study uses a non-parametric statistical analysis test method. More precisely, using the Spearman rank correlation test and the Wilcoxon test which cawas processed using SPSS Version 24 software. The results showed that Android-based educational media had a positive and significant effect on increasing the ability of grade 2 calistung and the results of the pretest trial showed an average of 68.18 and test results try the posttest show an average of 80.91. So, it can be concluded that the developed media is suitable for use as an educational tool and can improve calistung abilities in students’ learning competencies.